2022
DOI: 10.3390/ma15020509
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Loading Conditions and the Building Directions on the Mechanical Behavior of Biomedical β-Titanium Alloy Produced In Situ by Laser-Based Powder Bed Fusion

Abstract: In order to simulate micromachining of Ti-Nb medical devices produced in situ by selective laser melting, it is necessary to use constitutive models that allow one to reproduce accurately the material behavior under extreme loading conditions. The identification of these models is often performed using experimental tension or compression data. In this work, compression tests are conducted to investigate the impact of the loading conditions and the laser-based powder bed fusion (LB-PBF) building directions on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The chemical composition of the Ti42Nb titanium alloy investigated in this work is presented in Table 1. The LB-PBF parameters such as laser power, scanning speed, scanning spacing and layer thickness are described in a previous communication [5]. In order to investigate the possible impact of anisotropy, two building directions are used for manufacturing the compression and micro-cutting specimens.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of the Ti42Nb titanium alloy investigated in this work is presented in Table 1. The LB-PBF parameters such as laser power, scanning speed, scanning spacing and layer thickness are described in a previous communication [5]. In order to investigate the possible impact of anisotropy, two building directions are used for manufacturing the compression and micro-cutting specimens.…”
Section: Methodsmentioning
confidence: 99%
“…According to the results, the Ti42Nb microstructure is composed of non-columnar elongated β-grains oriented along the building direction. The as-LB-PBFed Ti42Nb microstructure shows the presence of un-melted or partially melted Nb particles (tomography analyses prove that the un-melted Nb particles represent less than 1% of the total amount of the Nb mass in the alloy see [5]) and spherical and elliptical pores distributed over all the specimens. These pores do not have preferential nucleation sites.…”
Section: Methodsmentioning
confidence: 99%
“…Among others, such more complicated 3D Ti substrates can be produced using additive manufacturing. However, though additive manufacturing offers the fabrication a plethora of different shapes, rather few studies have shown their modification with TNT layers. , These have been mainly pure Ti and biomedical Ti6Al4V alloy with the aim of their application as implants. However, also TiNb-based alloys have been shown to be producible using additive manufacturing, by using either selective laser melting (SLM)/laser-based powder bed fusion (LB-PBF), or laser engineered net shaping (LENS)/laser directed energy deposition. , Direct ink writing (DIW) has so far not been used for the production of TiNb alloys, although DIW has the advantage of simple powder blending, microstructural control through the sintering regimen, and using just the amount of metal powder needed for printing, thus reducing the environmental footprint and production cost …”
mentioning
confidence: 99%